IVISH: a Prototype of an Innovation in Scientific Knowledge of Hadith Using IV Techniques - F. Norasikin; I. Zawawi (Universiti Sains Islam Malaysia, 2024)
Information visualization plays an important role in enhancing human understanding during the process of data retrieval. Carefully crafted visual activities in information visualization techniques coupled with sound instructional design derived from learning theories can facilitate effective cognition of information for better understanding. Premised on the theories of learning and Alessi's and Trollip's development model, this research involved the development of a prototype of IVisH to help user process information during the retrieval of Islamic narrations of prophetic traditions. Usability testing was conducted involving 60 participants to measure the system design, system usage and system usability. The mean scores (out of maximum 4) were 3.42, 3.77, and 3.66 for the IVisH's system design, system usage and system usability respectively. These findings indicate that the complex chain of narrations of the prophetic traditions from the Islamic body of knowledge was made easier and flexible through the use of IVisH.